2019
DOI: 10.1016/j.chemphyslip.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of mycobacterial dimycoloyl diarabinoglycerol based on defined synthetic mycolic acids

Abstract:  Complex mixtures of natural dimycoloyl diarabinoglycerols isolated from mycobacteria have been shown to be potent immune signalling agents and potentially valuable antigens in the serodiagnosis of mycobacterial infections.  We now report the highly stereocontrolled synthesis of diacyl L-glycerol-(1'→1)-β-D-arabinofuranosyl-α-D-arabinofuranosides based on simple fatty acids and single defined synthetic mycolic acids.  NMR analysis confirmed that the synthetic core was identical to that in natural mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…were initially characterized from the MAIS complex (Watanabe et al 1992(Watanabe et al , 1999, but they are more widespread including M. tuberculosis (Rombouts et al 2012) and M. marinum (Elass-Rochard et al 2012). Synthetic studies indicated that these lipids are based on substituted glycerols with L-configuration (Ali et al 2019).…”
Section: Monomycoloyl Glycerols (Mmgs Gromms)mentioning
confidence: 99%
“…were initially characterized from the MAIS complex (Watanabe et al 1992(Watanabe et al , 1999, but they are more widespread including M. tuberculosis (Rombouts et al 2012) and M. marinum (Elass-Rochard et al 2012). Synthetic studies indicated that these lipids are based on substituted glycerols with L-configuration (Ali et al 2019).…”
Section: Monomycoloyl Glycerols (Mmgs Gromms)mentioning
confidence: 99%
“…We have already reported the synthesis of triarabinose dimycolates [25], of arabinoglycerol mycolates [19], and of DMAGs containing unique synthetic mycolic acids [26]. Although, so far, it has no reported bioactivity, we now report the extension of the methods used in those synthetic approaches to the synthesis of a single stereoisomer of tri-arabinofuranosyl glycerol (TAG) and of a series of stereo-defined DMTAG glycolipids (Figure 1), through esterification of the glycan with structurally defined synthetic MAs of α- and keto-classes [1,2].…”
Section: Introductionmentioning
confidence: 99%